Assessment of erectile dysfunction prevalence and associated factors in hypertensive men - RASHIDI M.; KISKAÇ N.; Meral D. K.; ÇAKMAK S.; DURUSOY E.; NART A.; CENGİZLİ D.; ÖZER E.; ASLAN M.; Kıskaç M. (My University, 2024)
Background. This study aimed to assess the prevalence of erectile dysfunction and identify associated factors among male patients with hypertension. Methods. A cross-sectional descriptive study was conducted. Data were gathered from 223 individuals aged 18 and above, solely diagnosed with hypertension. Information was collected through face-to-face questionnaires, personal identification forms, and the 5-question version of the International Sexual Function Index Scale. Results. Among the participants, 81.6% exhibited erectile dysfunction, with a mean total score of 18.72 ± 3.60 on the 5-question version of the International Index of Erectile Function Questionnaire, indicating a mild level of dysfunction. Older age, smoking, lower educational attainment, and use of beta blockers were associated with higher levels of erectile dysfunction (p < 0.05). Discussion. To mitigate modifiable risk factors influencing erectile dysfunction severity in hypertensive males, promoting healthy lifestyle choices, including diet, exercise, physiotherapy, and psychosocial support, as well as educating patients and their partners, could prove beneficial as non-pharmacological interventions.
Keywords: Tarımsal Bilimler; Ziraat; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Agricultural Sciences; Agriculture; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Tarım Ve Çevre Bilimleri (Age); Yaşam Bilimleri (Life); Tarım Bilimleri; Sinirbilim Ve Davranış; Moleküler Biyoloji Ve Genetik; Ziraat Mühendisliği; Sinir Bilimi; Biyokimya Ve Moleküler Biyoloji; Agriculture & Environment Sciences (Age); Life Sciences (Life); Neuroscience & Behavior; Molecular Biology & Genetics; Agricultural Engineering; Neurosciences; Biochemistry & Molecular Biology; Genel Sinirbilim; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Genel Tarım ve Biyoloji Bilimleri; General Neuroscience; General Biochemistry, Genetics and Molecular Biology; General Agricultural and Biological Sciences; Erectile dysfunction; Hypertension; Multidisciplinary approach; Risk factors